Contribution of nitrous acid to the atmospheric oxidation capacity in an industrial zone in the Yangtze River Delta region of China - J. Zheng; X. Shi; Y. Ma; Y. Ma; X. Ren; X. Ren; X. Ren; H. Jabbour; Y. Diao; Y. Diao; W. Wang; Y. Ge; et al. (Atmospheric Chemistry and Physics, 2020)
A suite of instruments was deployed to simultaneously measure nitrous acid (HONO), nitrogen oxides (NOx = NO + NO2), carbon monoxide (CO), ozone (O3), volatile organic compounds (VOCs – including formaldehyde, HCHO) and meteorological parameters near a typical industrial zone in Nanjing in the Yangtze River Delta (YRD) region of China from 1 to 31 December 2015. High levels of HONO were detected using a wet-chemistry-based method. HONO ranged from 0.03 to 7.04 ppbv with an average of 1.32±0.92 ppbv. Elevated daytime HONO was frequently observed with a minimum of several hundred parts per trillion by volume (pptv) on average, which cannot be explained by the homogeneous OH + NO reaction (POH+NO) and primary emissions (Pemission), especially during periods with high particulate matter (PM2.5) loadings. HONO chemistry and its impact on the atmospheric oxidation capacity in the study area were further investigated using a Master Chemical Mechanism (MCM) box model. The results show that the average hydroxyl radical (OH) production rate was dominated by the photolysis of HONO (7.13×106 molec. cm−3 s−1), followed by the ozonolysis of alkenes (3.94×106 molec. cm−3 s−1), the photolysis of O3 (2.46×106 molec. cm−3 s−1) and the photolysis of HCHO (1.60×106 molec. cm−3 s−1) during the campaign period, especially within plumes that originated from the industrial zone. Model simulations indicated that heterogeneous chemistry played an important role in HONO formation. The average nighttime NO2 to HONO conversion rate was determined to be ∼0.8 % h−1. A good correlation between nocturnal HONO∕NO2 and the product of particle surface area density (S∕V) and relative humidity (RH), S/V⋅<mtext>RH</mtext><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="44pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="20aec36cf7dcca4e8e9bafeb4313b5c7"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-20-5457-2020-ie00001.svg" width="44pt" height="14pt" src="acp-20-5457-2020-ie00001.png"/></svg:svg>, supports the heterogeneous NO2∕H2O reaction mechanism. The other HONO source, designated as Punknonwn, was about twice as high as POH+NO on average and displayed a diurnal profile with an evidently photo-enhanced feature, i.e., photosensitized reactions of NO2 may be an important daytime HONO source. Nevertheless, our results suggest that daytime HONO formation was mostly due to the light-induced conversion of NO2 on aerosol surfaces, whereas heterogeneous NO2 reactions on the ground surface dominated nocturnal HONO production. Our study indicated that an elevated PM2.5 level during haze events can promote the conversion of NO2 to HONO by providing more heterogeneous reaction sites, thereby increasing the atmospheric oxidation capacity, which may further promote the formation of secondary air pollutants.